Análise dos regimes próprios de Previdência Social dos municípios cearenses à luz do Índice de Desenvolvimento Previdenciário (IDP) – 2006 a 2008 - Oliveira, Adaíla Monteiro de (2011)
The study aims to analyze comparatively the level of development of the social security to the public sector (RPPSs - Regimes Próprios de Previdência Social) in cities of the State of Ceará – Brazil, from the period of 2006 to 2008, with available data on the Internet. To this end, it was made use of bibliography and data collection. The study dealt with information taken from the Annual Statement of Actuarial Valuations (DRAA – Demonstrativo Anual das Avaliações Atuariais), Social Security Statement and others. After collecting the data, it was performed the calculation of the indicators that construct the Social Security Development Index (IDP – Índice de Desenvolvimento Previdenciário). They are indicators of: 1)incorporated reserves (IRC – Indicador das Reservas Constituídas); 2) impairment of net current revenues (DPI – Dívida Pública Implícita); 3) pension plans maturity (IMP – Indicador de Maturidade Previdenciária); 4) commitment current (ICC – Indicador de Comprometimento Corrente); 5) commitment to personal tax (IFP – Indicador de Comprometimento Fiscal com Pessoal); and 6) legal framework (CRP – Certificado de Regularidade Previdenciária). The results of the study show that recent changes in legislation are allowing the construction and growth of sustainable pension systems, since most of the twenty-nine cities examined showed a change in level of pension plans development in the years 2006 to 2008, and suggests the inclusion of additional cost as another indicator of management of the IDP, whose influence was demonstrated by an econometric model.